Novel statistical methods for integrating genetic and stable isotope data to infer individual‐level migratory connectivity. Issue 16 (30th July 2013) - Rundel, Colin W.; Wunder, Michael B.; Alvarado, Allison H.; Ruegg, Kristen C.; Harrigan, Ryan; Schuh, Andrew; Kelly, Jeffrey F.; Siegel, Rodney B.; DeSante, David F.; Smith, Thomas B.; Novembre, John
Abstract Methods for determining patterns of migratory connectivity in animal ecology have historically been limited due to logistical challenges. Recent progress in studying migratory bird connectivity has been made using genetic and stable‐isotope markers to assign migratory individuals to their breeding grounds. Here, we present a novel Bayesian approach to jointly leverage genetic and isotopic markers and we test its utility on two migratory passerine bird species. Our approach represents a principled model‐based combination of genetic and isotope data from samples collected on the breeding grounds and is able to achieve levels of assignment accuracy that exceed those of either method alone. When applied at large scale the method can reveal specific migratory connectivity patterns. In Wilson's warblers (Wilsonia pusilla), we detect a subgroup of birds wintering in Baja that uniquely migrate preferentially from the coastal Pacific Northwest. Our approach is implemented in a way that is easily extended to accommodate additional sources of information (e.g. bi‐allelic markers, species distribution models, etc.) or adapted to other species or assignment problems.